Da crise da educação física escolar à cinesiologia humana na educação básica: estudo da apropriação da prática pedagógica dos professores - Ribeiro, Ricardo Yoshio Silveira (2019)
Physical Education, as a compulsory curriculum component in the school, must fulfill the same roles, assuming the same importance as the classical subjects, enabling students to study and learn knowledge related to this specific area. But nowadays, it is certainly a big challenge, as it is understood by society in general and by much of the school community as a distinct moment when compared to other curricular components, physical education can be both the most awaited moment. by some students as well as the most hated by others. The lack of clarity of the objectives of physical education at school perpetuates scenarios of a discipline that has no or little conceptual knowledge (theory), showing only practices often decontextualized related to training some sports, playing or playing. The research object that concerns us is the Human Kinesiology and the pedagogical practice in the Physical Education. In this sense, the core research question to which we intend to answer is: what is the epistemological contribution of Human Kinesiology to the pedagogical practice of teachers in Physical Education classes in elementary school II of private schools in the state of São Paulo? Our general objective is: To understand the epistemological contribution of Human Kinesiology to the pedagogical practice of Physical Education teachers and specific objectives: to analyze the appropriation of teachers who apply the conception of Human Kinesiology in Physical Education classes; to analyze the perception of teachers who apply the conception of Human Kinesiology in Physical Education classes. The epistemological model chosen is situated in a counter-hegemonic perspective, within the scope of post-critical and postcolonial theories. The methodological approach is qualitative, using as research tool, the interview with 7 Physical Education teachers working in the Greater São Paulo region and who already use Human Kinesiology in their practices. The conclusions of the research converge to a positive perception since all showed satisfactory knowledge of the conception of human kinesiology, its objectives, thematic blocks, and concepts that can be applied in their classes, in the stages of early childhood education, elementary and high school. At the same time they recognize major obstacles to its full implementation in the school curriculum due to a cultural tradition of Physical Education classes.